Class actions in Canada: cases, notes, and materials - Walker, Janet; Rosenberg, H. Michael; Kalajdzic, Jasminka (Emond Montgomery Publications Limited, 2024)
"Class Actions in Canada: Cases, Notes, and Materials, 3rd Edition leverages the experience of practising lawyers from eight Ontario law firms as well as chartered arbitrator and law professor Janet Walker. This casebook highlights key case law and current legislative regimes guiding the certification of class actions, the determination of representation, and the approval of settlements. It explores procedural challenges, including the complexities of multijurisdictional actions."– Provided by publisher.